Reasons behind the rising wave of Religious Extremism and Domestic Terrorism in Pakistan: A Study in Context of Post 9/11 Pak-US Partnership - Dr. Saqib Khan Warraich; Dr. Muhammad Mumtaz Ali Khan; Imran Alam (Al-Qamar, 2018)
This article assesses the post 9/11 period and Pak-US partnership in the war against terrorism. It explores the assumptions that Pakistan’s troubles increased after becoming ally of USA. It argues that militants, militant organizations all take this partnership against Islam and Pakistan becomes a worst victim of a domestic terrorism. The concept of Jihād in Islam is negatively used by the militant organizations against the state. It then goes on to illustrate that Musharraf’s enlightened moderation failed and Tehrīk-e-Nifāz-e-Sharīat-ie-Mohammadī reactivated. The article ends with the impact of peace deal with militants that proved a bad idea.